If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + (5x) = 50 + (10x) Solving 25 + (5x) = 50 + (10x) Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(-10x)' to each side of the equation. 25 + (5x) + (-10x) = 50 + (10x) + (-10x) Combine like terms: (5x) + (-10x) = -5x 25 + -5x = 50 + (10x) + (-10x) Combine like terms: (10x) + (-10x) = 0 25 + -5x = 50 + 0 25 + -5x = 50 Add '-25' to each side of the equation. 25 + -25 + -5x = 50 + -25 Combine like terms: 25 + -25 = 0 0 + -5x = 50 + -25 -5x = 50 + -25 Combine like terms: 50 + -25 = 25 -5x = 25 Divide each side by '-5'. x = -5 Simplifying x = -5
| 10pq+8p= | | -3h-4=h-8 | | 4=(m+13) | | 81-x=93-2x | | 5+-11t=7(5+-2t) | | 8x^2+7x-4=0 | | 7g(-3h+1)= | | 81-x=93-x | | 2a+2=a+4 | | 79-(101-5y)=2(101-5y)+y | | 6.5(x-4)=-0.5x+30 | | 5=(x+8) | | -5x+6y=30 | | 19x=12x | | 11x+2=5x+10+58 | | -5-x=1+2x | | 4d=7-7 | | 8x+2+70+60= | | -5(a-6)+2a=9 | | (3x-6y-1)+(-x+y+10)= | | 3w+10=-3+8w-9w | | 4(2y+1)-2y=-26 | | 1/3(102-12c)=5(3c+10) | | 5x-x-3=2x+6 | | M-3=7m-21 | | 4n-(7-6n)=13 | | 6x+3=3(2x+3) | | 2x-11=23 | | 3x=52 | | (9x-8y-11)-(5x-9y+1)= | | -8=1.3x+x | | 10=-2.3(4x+5) |